THE SOUK OF EL KHROUB: AN ECONOMIC AND SOCIAL PILLAR IN RESPONSE TO RECENT COMMERCIAL TRANSFORMATIONS - Mohamed Amine Khenchouche,; Nassima Khenchouche,; Karima Benhalilou, (International Journal of Innovative Technologies in Social Science, 2024)
At the heart of El Khroub’s urban dynamics, the traditional market (souk) continues to play a significant economic and social role, despite facing recent urban transformations and the challenges posed by contemporary development types. Over a six-month period, encompassing 52 working days of the souk (Thursdays and Fridays), we conducted an in-depth sociological survey using a detailed questionnaire with a representative sample of 400 individuals. The sample was selected using the Krejcie and Morgan method, combined with the quota sampling method (Moser & Kalton, 1971), to ensure that our sample reflected the diversity of stakeholders involved in the souk. The population was divided into four main strata: merchants, long-time visitors of the souk, local government members, and buyers. In addition to this survey, we conducted direct interviews with officials involved in the management of the souk, such as the municipal treasury officer and the current lessee of the souk, while also consulting the relevant specifications. This thorough assessment allowed us to fully understand the socio-economic characteristics and dynamics of this market.Thus, although initially centered on livestock trade, the souk of El Khroub has lost much of its former vitality ; it remains a crucial economic hub for local businesses and an essential social gathering point, despite the lack of relevant initiatives from municipal services to invigorate it and restore its former prominence. This paper highlights the critical importance of the El Khroub souk as an economic and social space, which requires the implementation of a strategy that would ensure its prosperity and ability to face current economic challenges. Therefore, we present a scenario to address these issues.